Flag leaf cell wall functional groups and components play a crucial role in the accumulation and translocation of Cd in rice grain via foliage application of humic acid - Xiao Deng; Bin Chen; Yixuan Chen; Lu Jiang; Yumin Hu; Yang Yang; Xiangmin Rong; Liang Peng; Qingru Zeng (Ecotoxicology and Environmental Safety, 2022)
Devising a low-cost and effective strategy to reduce Cd contamination of brown rice is critical to achieve the safe production of rice grain for human consumption. Accordingly, here field experiments were conducted at two sites to evaluate the effects of applying humic acid (HA) to foliage twice, at the booting and full heading stage, on diminishing the translocation of cadmium (Cd) into rice grains. Besides measuring the Cd subcellular distribution in the flag leaf and the polysaccharide composition of the cell wall, the latter’s types and concentrations of functional groups were quantitatively analyzed by potentiometric titration and fitted by a surface complexation model. The results demonstrated that applying HA to leaves not only increased the rice yield but also reduced the Cd concentration in brown rice by 35.48–39.74% when using an application rate of just 600 g/ha. The HA treatment augmented Cd fixation in flag leaves, reduced the Cd translocation to rachis and brown rice, and increased the subcellular distribution of Cd in flag leaf cell wall. Furthermore, the Cd concentration in the pectin and hemicellulose 1 of cell wall increased by 33.00% and 25.73%, respectively. Besides those effects, foliar spraying of HA induced a greater abundance of carboxyl, hydroxyl, and amino groups on the cell wall, allowing for more sites to be involved in the binding of Cd, thereby promoting the immobilization of Cd in the flag leaf, and ultimately reducing the remobilization of Cd into the grain. Thus, foliage application of HA may offer a promising and cost-effective tactic for the remediation and continued use of Cd-contaminated paddy soils. Capsule: Foliage application of humic acid promoted the deposition of Cd in the cell wall of rice flag leaf, thereby enhancing the immobilization of Cd and ultimately reducing the remobilization of Cd into the grain